2010
DOI: 10.1590/s1808-86942010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de citocinas da polipose nasossinusal na Fibrose Cística comparado com indivíduos sem doenças nasossinusais

Abstract: 0,05). Menores valores de IFNy¬ (p=0,03) e forte tendência de aumento de IL¬4 (p=0,06) foram observados no grupo Fibrose Cística. CONCLUSÃO: As células inflamatórias e estruturais podem produzir RNA mensageiro para IL¬4, bloqueando a produção de outras citocinas com IFN-y¬, sugerindo a participação destes mecanismos na formação dos pólipos da Fibrose Cística.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In this study, no differences of salivary IL-8 and IL-6 were observed between CF patients with NP and without NTH/NP. Accordingly, a cross-sectional study reported similar levels of IL-8 and IL-6 mRNA in CF patients with and without NP [18]. We observed that salivary TNF-α was significantly reduced in patients with NP, which is the most advanced phase of the sinonasal disease.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In this study, no differences of salivary IL-8 and IL-6 were observed between CF patients with NP and without NTH/NP. Accordingly, a cross-sectional study reported similar levels of IL-8 and IL-6 mRNA in CF patients with and without NP [18]. We observed that salivary TNF-α was significantly reduced in patients with NP, which is the most advanced phase of the sinonasal disease.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, an increase of IL-8 and IL-5 was observed in the nasal secretions of patients with CF compared to healthy subjects, but no significant differences were found between patients with and without NP [17]. In addition, Nunes et al [18] reported similar mRNA levels of IL-8 and IL-6 in CF patients with and without NP. On the other hand, the cytokine profile in airway fluids from CF patients with NTH and the differences of cytokine profile between CF patients with NP and NTH have not been well investigated.…”
Section: Introductionmentioning
confidence: 94%
“…To better understand the pathogenic mechanisms of nasal polyps in CF, several studies have tried to characterize the inflammatory microenvironment, cytokines, adhesion molecules, and ionic transport. A Brazilian study conducted by Nunes and coworkers [ 38 ] analyzed the expression of messenger ribonucleic acid (mRNA) for cytokines IL4, IL5, IL6, IL8, GM-CSF, and INF-gamma in patients with CF, who had nasal polyposis, and in a control group, using reverse transcription-polymerase chain reaction (RT-PCR). The resulting expression of mRNA for IL5, IL6, IL8, and GM-CSF was similar in the group with CF polyposis and in the control group.…”
Section: Profile Of Cytokines In Sinonasal Polyposis In Cfmentioning
confidence: 99%
“…These bacteria stimulated production of IL4 by Th2 cells. The results would reflect intense inflammation with an increase in the eosinophilic cationic protein, total IgE, intermediated by the increase of IL4 and the low INF-gama [ 38 ].…”
Section: Profile Of Cytokines In Sinonasal Polyposis In Cfmentioning
confidence: 99%